Continuous Control of Microbiological Contamination of Juice in a Sugar Extractor - Iciek, Jan; Ludwicki, Marek; Błaszczyk, Ilona (Recent Advances in Food Nutrition & Agriculture, 2023)
The paper discusses the causes and needs of controlling the level of microbiological contamination of juice in a vertical extractor and the methods to control the level of contamination. The requirements and possibilities for controlling the microbiological contamination level of juice extracted from the vertical extractor are described using redox potential value measurement. Aerating the extractor in a controlled manner, regulating the pH level of the juice, and implementing one of the presented proposals on how to record the measurement results will automatically regulate microbiological contamination levels of the juice in the tower extractor.
Keywords: potential redox sensor and meter